Structure ofd d‐alanine‐d d‐alanine ligase fromYersinia pestis Yersinia pestis: nucleotide phosphate recognition by the serine loop. Issue 1 (1st January 2016) - Tran, Huyen-Thi; Hong, Myoung-Ki; Ngo, Ho-Phuong-Thuy; Huynh, Kim-Hung; Ahn, Yeh-Jin; Wang, Zhong; Kang, Lin-Woo
Abstract : Five crystal structures ofd d ‐alanine‐d d ‐alanine ligase from Y. pestis Y. pestis have been determined at 1.7–2.5 Å resolution: apo, AMP‐bound, ADP‐bound, adenosine 5′‐(β, γ‐imido)triphosphate‐bound, andd d ‐alanyl‐d d ‐alanine‐ and ADP‐bound structures. The serine loop is mainly responsible for the conformational change in the substrate nucleotide phosphates. Abstract : d d ‐Alanyl‐d d ‐alanine is an essential precursor of bacterial peptidoglycan and is synthesized byd d ‐alanine‐d d ‐alanine ligase (DDL) with hydrolysis of ATP; this reaction makes DDL an important drug target for the development of antibacterial agents. Five crystal structures of DDL from Yersinia pestis Yersinia pestis (YpDDL) were determined at 1.7–2.5 Å resolution: apo, AMP‐bound, ADP‐bound, adenosine 5′‐(β, γ‐imido)triphosphate‐bound, andd d ‐alanyl‐d d ‐alanine‐ and ADP‐bound structures. YpDDL consists of three domains, in which four loops, loop 1, loop 2 (the serine loop), loop 3 (the ω‐loop) and loop 4, constitute the binding sites for twod d ‐alanine molecules and one ATP molecule. Some of them, especially the serine loop and the ω‐loop, show flexible conformations, and the serine loop is mainly responsible for the conformational change in substrate nucleotide phosphates. Enzyme‐kinetics assays were carried out for both thed d ‐alanine and ATP substrates and a substrate‐binding mechanism was proposed for YpDDL involving conformational changes of the loops.